Rancang Bangun Alat Pendeteksi Kematangan Buah Durian - Badri, Nurul; Jaya, Putra (TSAQOFAH, 2025)
This study aims to design and develop a durian ripeness detection device based on an electronic nose system using an engineering design approach. The system employs the MQ-135 gas sensor as the primary detector to identify alcohol levels emitted by durian fruit, along with an ultrasonic sensor that automatically activates the system. An Arduino microcontroller functions as the control center, programmed in C language. When durian is detected by the ultrasonic sensor, the MQ-135 sensor measures the alcohol concentration; if it exceeds the 3% threshold, the system activates a green LED and buzzer to indicate ripeness, whereas levels below the threshold suggest the fruit is unripe. Experimental testing was conducted on durians at various ripeness levels, with data analyzed descriptively. Results indicate that the device can distinguish between ripe and unripe durians with an accuracy rate of 86.7%. The device is non-destructive, portable, and efficient, making it highly suitable for use by farmers, collectors, and traders in durian sorting and distribution processes. The study concludes that an Arduino-based electronic nose system offers a practical innovation for enabling the public to assess durian ripeness more accurately and conveniently.